Biotransformation of 11-ketoprogesterone by Filamentous Fungus, Fusarium lini - Al-Maruf, M. A.; Khan, N. T.; Saki, M. A. A.; Choudhary, M. I.; Ali, M. U.; Islam, M. A. (Journal of Scientific Research, 2011)
Microbial transformation of 11-ketoprogesterone (1) by the filamentous fungi Fusarium lini was investigated. Biotransformation of 1 with F. lini resulted in the production of ten oxidative metabolites (2-11). Structures of these metabolites were deduced by spectroscopic analysis and seven of them, 5-11, were found to be new metabolites. Keywords: 11-Ketoprogesterone; Steroid; Microbial transformation; Hydroxylation; Filamentous fungi; Fusarium lini. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v2i2.6221 J. Sci. Res. 3 (2), 347-356 (2011)